Real and reactive power forecast model for long term demand in peninsular Malaysia - Abdullah S.W.; Isa A.M.; Osman M. (2023)
In planning a power system, load forecasting is a crucial initial step in order to make sure that power delivered will meet the target timely and adequately. This paper aims to determine the best model to estimate the demand, real and reactive, in the twelve states of Peninsular Malaysia. The two methods that will be used for evaluation are Autoregressive Integrated Moving Average (ARIMA) and Regression. Results will be compared to find the best model based on statistical parameter comparison.